2011
DOI: 10.1016/j.physletb.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The most general cosmological dynamics for ELKO matter fields

Abstract: Not long ago, the definition of eigenspinors of charge-conjugation belonging to a special Wigner class has lead to the unexpected theoretical discovery of a form of matter with spin 1 2 and mass dimension 1, called ELKO matter field; ELKO matter fields defined in flat spacetimes have been later extended to curved and twisted spacetimes, in order to include in their dynamics the coupling to gravitational fields possessing both metric and torsional degrees of freedom: the inclusion of non-commuting spinorial cov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 26 publications
0
54
0
Order By: Relevance
“…Elko in the presence of torsion has been a subject of several insightful papers by Luca Fabbri. We refer the reader to these and related publications [93][94][95][96][97][98][99]. Cosmological solutions of 5D Einstein equations with Elko condensates were obtained by Tae Hoon Lee where it was found that there exist exponentially expanding cosmological solution even in the absence of a cosmological constant [100].…”
mentioning
confidence: 99%
“…Elko in the presence of torsion has been a subject of several insightful papers by Luca Fabbri. We refer the reader to these and related publications [93][94][95][96][97][98][99]. Cosmological solutions of 5D Einstein equations with Elko condensates were obtained by Tae Hoon Lee where it was found that there exist exponentially expanding cosmological solution even in the absence of a cosmological constant [100].…”
mentioning
confidence: 99%
“…The characterization of exotic singular spinor fields in Lounesto's classes has introduced new fermions, including mass dimension one matter quantum fields, that have been studied in [12], with immediate physical applications to the problem of dark matter, after the work in [13][14][15], with applications to the study of Hawking radiation [16]. Other aspects of spinors fields classifications can also be found in Ref.…”
Section: General Bilinear Covariants and Spinor Field Classesmentioning
confidence: 99%
“…From the phenomenological point of view, Elko can be produced by Higgs interactions [26], and realise a particle, whose symmetries are governed by the Very Special Relativity (VSR) [37]. Some attempts to detect Elko at the LHC have been moreover proposed [26], as well as promising applications in cosmology [38,39].…”
Section: Introductionmentioning
confidence: 99%